Key concepts in rapid reviews: an overview - Devane, Declan; Hamel, Candyce; Gartlehner, Gerald; Nussbaumer-Streit, Barbara; Griebler, Ursula; Affengruber, Lisa; Saif-Ur-Rahman, KM; Garritty, Chantelle (Journal of clinical epidemiology, 2024)
Rapid reviews have gained popularity as a pragmatic approach to synthesize evidence in a timely manner to inform decision-making in healthcare. This article provides an overview of the key concepts and methodological considerations in conducting rapid reviews, drawing from a series of recently published guidance papers by the Cochrane Rapid Reviews Methods Group. We discuss the definition, characteristics, and potential applications of rapid reviews and the trade-offs between speed and rigor. We present a practical example of a rapid review and highlight the methodological considerations outlined in the updated Cochrane guidance, including recommendations for literature searching, study selection, data extraction, risk of bias assessment, synthesis, and assessing the certainty of evidence. Rapid reviews can be a valuable tool for evidence-based decision-making, but it is essential to understand their limitations and adhere to methodological standards to ensure their validity and reliability. As the demand for rapid evidence synthesis continues to grow, further research is needed to refine and standardize the methods and reporting of rapid reviews.